Jokes and Riddles - Glen Singleton (Illustrator)
Do you love uproarious riddles, outrageous one-liners and riotous jokes? Pocket Pal*: Jokes & Riddles will always be on hand to provide you with awesome selection of jokes that will have you in hysterical fits of laughter with no end in sight!